INSTITUTE OF PROFESSIONAL MOTIVATED JUDGMENT TRENDS FURTHER DEVELOPMENT AND PLACE IN THE SYSTEM OF BANKING LAW AND LEGISLATION - E. E. Frolova; E. V. Karmadonova (Модернизация, инновация, развитие, 2015)
The article is devoted to comprehensive analysis of the concept of professional motivated judgment applied regulator (Bank of Russia) in respect of a credit institution. This concept (category) is considered in a variety of ways: as the approach used in international banking practice, as an institution of banking supervision, assessment, assign to the Bank of Russia credit institution on the basis of the analysis of numerous fi nancial parameters of activity of the latter, ownership structure, the risks taken, as well as objective economic factors. The article discusses the main directions of banking supervision, in which there are elements of professional professional judgment and objectives of its issuance.